2020
DOI: 10.1111/jocs.14779
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral femoral venoarterial extracorporeal membrane oxygenation as bridge to heart‐lung transplant omne iter incipit primus

Abstract: Heart‐lung transplant (HLT) is a widely accepted modality for certain patients with advanced and refractory cardiopulmonary disease. Some of these patients are critically ill on the transplant waiting list, and venoarterial extracorporeal membrane oxygenation (VA‐ECMO) can be used as a bridge to transplantation. Although the experience with ECMO as a bridge to lung transplant is promising, there is limited evidence to use ECMO as a bridge to HLT. Femoral cannulation remains a concern for ambulation given the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Peripheral, femorally inserted VA-ECMO cannulation provides a rapid method for the restoration of end-organ perfusion. While previous reports have demonstrated that patients can ambulate while on VA-ECMO, 2 , 3 , 4 it is also clear peripherally inserted VA-ECMO increases afterload, which may have adverse consequences. Specifically in the severely impaired heart, elevated LV pressures may lead to pulmonary edema, ventricular overdistention, and myocardial ischemia, further propagating cardiac injury.…”
Section: Discussionmentioning
confidence: 88%
“…Peripheral, femorally inserted VA-ECMO cannulation provides a rapid method for the restoration of end-organ perfusion. While previous reports have demonstrated that patients can ambulate while on VA-ECMO, 2 , 3 , 4 it is also clear peripherally inserted VA-ECMO increases afterload, which may have adverse consequences. Specifically in the severely impaired heart, elevated LV pressures may lead to pulmonary edema, ventricular overdistention, and myocardial ischemia, further propagating cardiac injury.…”
Section: Discussionmentioning
confidence: 88%
“…Venovenous extracorporeal membrane oxygenation (VV‐ECMO) is increasingly being used to bridge acutely deteriorating candidates to LTx as it can allow critically ill recipients to remain eligible for LTx while reducing pretransplant deconditioning 4–8 . In particular, VV‐ECMO as a bridge to transplantation (BTT) can facilitate early ambulation, thus improving their condition, and may mitigate detrimental intensive care unit complications including weakness, delirium, and ventilator‐associated pneumonia or lung injury 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Current ECMO therapy is more convenient and mobile than previously. Multiple studies have reported the feasibility and safety of ambulating patients with femoral cannulas 2–5 …”
Section: Introductionmentioning
confidence: 99%